Contribuição ao estudo da Erosão-corrosão de um aço de baixo carbono na presença de água contendo 3,5% de sal, areia e inibidor de corrosão - Magalhães, Luciano da Rocha (2018)
Deep water oil production imposes several challenges for oil and gas companies, and among them, the wear suffered in the interior of the transportation pipelines due to the action of produced water (high salt content), gases and particulates, especially produced sand. The objective of this work was to study the erosion-corrosion of a low carbon steel in a flowloop under dynamic conditions: fluid with 3.5% NaCl, sand at a concentration of 40 g cm-3 and addition of a corrosion inhibitory substance, with a main focus on observing the possible interaction between the erosive agent and the inhibitor. For this purpose, we performed erosion-corrosion tests in a closed circuit of pipes of four inches of internal diameter and we applied the corrosion rate measurement techniques of mass loss coupons, linear polarization resistance and electrochemical impedance spectroscopy. We also monitored the concentration of inhibitor in the fluid and the modifications on the surface of the specimens by scanning electron microscopy. At the end of this work, we concluded that the steel presents a corrosion rate of 3.5 mm year-1 without the addition of inhibitor and 0.4 mm year-1 with the addition of inhibitor. We did not observe any direct interaction between the sand and corrosion inhibitor that could compromise the efficiency of the substance. We also concluded that electrochemical techniques can be successfully employed in dynamic conditions by means of a cell specifically designed for pipelines. The results showed that the cell and the technique were able to identify the synergistic effect of erosion-corrosion in the bottom of the pipe and also the action of the corrosion inhibitor.